Make your query anonymous with oblivious transfer - Gupta V.; Vineeth T.S.; Aggarwal V. (My University, 2025)
In this paper, we will consider a two party computation model in which the client wishes to make a query to the server, but doesn't want to reveal his query to anyone. Existing solutions are based on Oblivious Transfer, k - Anonymous Oblivious Transfer and Deterministic Encryption and Bloom Filers. Here, we propose two protocols first being the k∗1 - Anonymous Oblivious Transfer protocol and second, the combination of Symmetric Key Encryption (Block Cipher) and k∗1 - Anonymous Oblivious Transfer protocol which we will apply to approach the anonymous query problem where the server cannot tell which record the querying client wants from the records and neither the client could receive anything but the record pertaining to his query. Our protocol can achieve anonymity theoretically and is practical in situations where privacy is given more priority than speed. © 2015 ACM.